Safety of long-term denosumab therapy: results from the open label extension phase of two phase 3 studies in patients with metastatic breast and prostate cancer - Stopeck, Alison T.; Fizazi, Karim; Body, Jean-Jacques; Brown, Janet E.; Carducci, Michael; Diel, Ingo; Fujiwara, Yasuhiro; Martín, Miguel; Paterson, Alexander; Tonkin, Katia; Shore, Neal; Sieber, Paul; et al. (Supportive care in cancer, 2016)
Purpose Zoledronic acid (ZA) or denosumab treatment reduces skeletal-related events; however, the safety of prolonged therapy has not been adequately studied. Here, we describe safety results of extended denosumab therapy in patients with bone metastases from the open-label extension phase of two phase 3 trials. Methods Patients with metastatic breast or prostate cancer received subcutaneous denosumab 120 mg Q4W or intravenous ZA 4 mg Q4W in a double-blinded fashion. Denosumab demonstrated superior efficacy in the blinded treatment phase; thus, patients were offered open-label denosumab for up to an additional 2 years. Results Cumulative median (Q1, Q3) denosumab exposure was 19.1 (9.2, 32.2) months in the breast cancer trial ( n = 1019) and 12.0 (5.6, 21.3) months in the prostate cancer trial ( n = 942); 295 patients received denosumab for >3 years. No new safety signals were identified during the open-label phase, or among patients who switched from ZA to denosumab. During the blinded treatment phase, exposure-adjusted subject incidences of osteonecrosis of the jaw (ONJ) were 49 (1.9 %) and 31 (1.2 %) in the denosumab and ZA groups, respectively. In total, 32 (6.9 %) and 25 (5.5 %) new cases of ONJ (not adjusted for exposure) were reported for patients continuing and switching to denosumab, respectively. The incidences of hypocalcemia were 4.3 and 3.1 %, in patients continuing and switching to denosumab, respectively. Conclusion These results describe the safety profile of denosumab after long-term exposure, or after switching to denosumab from ZA. No new safety signals were identified. Hypocalcemia rates were similar in the blinded treatment and open-label phases. ONJ rates increased with increasing exposure to antiresorptives, consistent with previous reports.